Kualitas Citra CT Abdomen Non Kontras Berdasarkan Variasi Rotation Time (Studi Penelitian dengan Menggunakan Phantom) - Dyah Arum Larasati; Gatot Murti Wibowo; Sri Mulyati (Jurnal Imejing Diagnostik (JImeD), 2017)
Backgroud: Has conducted research in Radiology Department of RS Telogorejo Semarang regarding image quality of CT Abdomen non contrast based on variations of rotation time in phantom, especially noise and spatial resolution. This study was conducted to determine the difference in rotation time variation of the image quality (noise and spatial resolution) on a non-contrast CT abdomen and know the value rotation time is used in order to produce optimal image quality with the variations of the rotation time of 0.5 s, 0, 6 s, 0.7 s, 0.8 s, 0.9 s and 1.0 s.Methods: This research is a quantitative study with an experimental approach. Data have been collected from December 2016 to January 2017 in Radiology Department of RS Telogorejo Semarang. CT abdomen non-contrast examinations performed by using the modality of 64 slice CT scan and the data collected by assessing noise and spatial resolution in phantom. Further, data were tested with data normality test then the statistical test by Kruskal Wallis test has been used to determine the difference in image quality was noise and spatial resolution on non-contrast abdominal CT followed by Post Hoc test Mann Whitney on spatial resolution to determine a significant difference between the variation of rotation time .Results: The results of this study showed significant differences in spatial resolution with p value 0.001 and there were no significant difference in the value of noise with p value 0.001 non-contrast abdominal CT.Conclusion: Values optimal rotation time for CT Abdomen non contrast with variation of the rotation time are 0.5 s, 0.6 s, 0.7 s, 0.8 s, 0.9 s and 1.0 s for the spatial resolution is 0.6 s and 1.0 s for the noise.